Determinants of export performance - Heiko Körner (Intereconomics, 1974)
Comparative advantage, government incentives and entrepreneurial dynamics as determinants of a country's export performance are discussed in this article. The author's particular attention is focussed on the present situation and future perspectives of the less developed countries.
Keywords: 330; Foreign Trade